A reconfigurable multi-mode mobile parallel robot. (May 2017) - Tian, Yaobin; Zhang, Dan; Yao, Yan-An; Kong, Xianwen; Li, Yezhuo
Abstract: In this paper we put forward the idea of deforming the geometry of a parallel mechanism such that it can operate either as an equivalent rolling robot or quadruped robot. Based on it, we present a novel mobile parallel robot that can change its locomotion modes via different equivalent mechanisms. The robot is in essence a four-arm parallel mechanism in which each arm contains five revolute (R) joints. The axes of the three internal R joints in any arm are parallel and are orthogonal to those of the end joints. Based on singularity and deformation analysis, we show that the upper platform has four practical operation modes, (i.e., translation, planar, rotational, and locked-up modes). Using these operation modes, the robot can realize rolling, tumbling and quadruped locomotion modes by deforming into switching states. The switching configurations of the robot are further identified in which the robot can switch among different locomotion modes, such that the robot can choose its mode to adapt complex terrains. To verify the functionality of the robot, we present the results of a series of simulations, and perform the locomotion modes' experiments on a manufactured prototype. Highlights: A novel mobile robot constructed by a four-arm parallel mechanism is presented, which can operate either as an equivalent rolling robot or quadruped robot. Four typical operation modes are presented based on the singularity positions of the robot. Rolling, tumbling, and quadruped gaits are given and simulated. Experimental results of physical prototypes of the robot are presented.